A functional interaction between GRP78 and Zika virus E protein - Sarawut Khongwichit; Wannapa Sornjai; Kunlakanya Jitobaom; Mingkwan Greenwood; Michael P. Greenwood; Atitaya Hitakarun; Nitwara Wikan; David Murphy; Duncan R. Smith (Scientific Reports, 2021)
Abstract Zika virus (ZIKV) is a mosquito-transmitted virus that has caused significant public health concerns around the world, partly because of an association with microcephaly in babies born to mothers who were infected with ZIKV during pregnancy. As a recently emerging virus, little is known as to how the virus interacts with the host cell machinery. A yeast-2-hybrid screen for proteins capable of interacting with the ZIKV E protein domain III, the domain responsible for receptor binding, identified 21 proteins, one of which was the predominantly ER resident chaperone protein GRP78. The interaction of GRP78 and ZIKV E was confirmed by co-immunoprecipitation and reciprocal co-immunoprecipitation, and indirect immunofluorescence staining showed intracellular and extracellular co-localization between GRP78 and ZIKV E. Antibodies directed against the N-terminus of GRP78 were able to inhibit ZIKV entry to host cells, resulting in significant reductions in the levels of ZIKV infection and viral production. Consistently, these reductions were also observed after down-regulation of GRP78 by siRNA. These results indicate that GRP78 can play a role mediating ZIKV binding, internalization and replication in cells. GRP78 is a main regulator of the unfolded protein response (UPR), and the study showed that expression of GRP78 was up-regulated, and the UPR was activated. Increases in CHOP expression, and activation of caspases 7 and 9 were also shown in response to ZIKV infection. Overall these results indicate that the interaction between GRP78 and ZIKV E protein plays an important role in ZIKV infection and replication, and may be a potential therapeutic target.